Analisis Tingkat Kesehatan Bank dan Dampaknya terhadap Peningkatan Jumlah Nasabah - Suyatna, Nano; Mu’minin, Ayi Mi’razul (Universitas Ma'soem, 2021)
The background of this research is the fluctuation in the value of the ratio of CAR, KAP, ROA, IGA and LDR will affect the performance of a bank, so it is necessary to look at the level of health which will have an impact on increasing the number of customers. The purpose of this study was to determine the health level of BPRS Al Ma'soem using the CAMEL (Capital, Asset, Management, Earning, Liquidity) method and its impact on increasing the number of customers. The type of research uses secondary data with the object of research, namely the financial statements of BPRS Al Ma'soem. The population is all the financial statements of BPRS Al Ma'soem, while the sample is the financial statements of BPRS Al Ma'soem for the 2016-2020 period with the type of sample using purposive sampling. Data collection techniques include literature study and documentation. While the method used is descriptive qualitative using the Milles and Huberman model including: data collection, data reduction, data presentation and conclusions and using the CAMEL method. The results show that the health level of BPRS Al Ma'soem using CAMEL analysis in terms of capital, assets, earnings and liquidity in 2016 with very good predicates, 2017 and 2018 with good predicates, 2019 with very good predicates, and 2020 with good predicate. However, from a management perspective, from 2016-2020, it received a pretty good predicate.